Les femmes dans l’histoire du duché de Normandie - Elisabeth Van Houts (Tabularia)
Instead of concluding that Norman women did not play any role in the process of writing history, I should like to suggest that there were other ways in which they could be involved with the history of their families. They acted as channels of historical knowledge between the generations. Aristocratic women, preoccupied with the past, the present and the future, stimulated the production of historical and prophetical narratives. Three dossiers in particular will be discussed here: the grant of the castle of Le Homme (Cotentin) by Countess Adeliza of Burgundy to the nuns of Holy Trinity at Caen in 1075, the two versions of the foundation narrative of the church of St Martin at Auchy dating to the late eleventh century, and manuscript Paris BN Lat. 5390 (Ralph Glaber, Life of William of Volpiano; Adso of Montier-en-Der, The Origin and Time of the Antichrist and the sibyline prophecy) copied between 1060 and 1070.